2022
DOI: 10.18332/ejm/147444
|View full text |Cite
|
Sign up to set email alerts
|

Why use Appreciative Inquiry? Lessons learned during COVID-19 in a UK maternity service

Abstract: Choosing the 'right' research method is always an important decision. It affects the type of study questions that can be answered. In addition, the research method will have an impact on the participants -how much of their time it takes, whether the questions seem important to them and whether there is any benefit in taking part. This is especially important when conducting research with staff in health services. This article is a reflection on the process of using Appreciative Inquiry (AI) in a study that exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The study authors reported a potential negative aspect of Appreciative Inquiry when participants were unable to find positive elements in their current work situation or had little proposals to improve their situation. Similar findings were also reported by Arnold et al, (2022), who used an Appreciative Inquiry to explore staff well-being in a UK maternity unit during COVID-19.…”
Section: Criticisms Of Appreciative Inquirysupporting
confidence: 82%
See 3 more Smart Citations
“…The study authors reported a potential negative aspect of Appreciative Inquiry when participants were unable to find positive elements in their current work situation or had little proposals to improve their situation. Similar findings were also reported by Arnold et al, (2022), who used an Appreciative Inquiry to explore staff well-being in a UK maternity unit during COVID-19.…”
Section: Criticisms Of Appreciative Inquirysupporting
confidence: 82%
“…Internationally, Appreciative Inquiry is also being increasingly adopted within the midwifery profession as a driver to understand and implement positive change. (Arnold et al, 2022;Dewar et al, 2020;Maxwell, Black, & Baillie, 2015;Sidebotham et al, 2015).…”
Section: Why Does Appreciative Inquiry Methodology Suit This Research?mentioning
confidence: 99%
See 2 more Smart Citations
“…The right questions have the propensity for participants to focus from an alternative perspective. Recalling positive experiences also has a progenitive potential to forge resilience and foster trust and openness to creativity (Arnold et al , 2022).…”
Section: Methodsmentioning
confidence: 99%